THE ROLE OF STRUCTURAL ENGAGEMENT IN INTER-RELIGIOUS DIALOGUE: IN THE CASE OF THE INTER-RELIGIOUS CONFLICT IN GPDI SEMANU, GUNUNGKIDUL - Puteri, Perdana Aysha (Jurnal Studi Agama dan Masyarakat, 2021)
The case of expulsion of a pastor at Semanu Gunungkidul GPdI church was resolved through mediation by the regional assistant. The conflict was triggered by the issue of Christianization by the pastor of GPdI Semanu. Today the conflict has ended, but it still leaves prejudice among religious leaders and structural officials in the area. The main data were interviews with those who directly involved in conflict and in efforts to resolve it. They were Muslim and Christian religious leaders, FKUB, sections of local government that were directly dealt with